2021
DOI: 10.3389/fmicb.2021.649981
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impacts of Water Table and Temperature on Bacterial Communities in Pore Water From a Subalpine Peatland, Central China

Abstract: The level of water table and temperature are two environmental variables shaping soil bacterial communities, particularly in peatland ecosystems. However, discerning the specific impact of these two factors on bacterial communities in natural ecosystems is challenging. To address this issue, we collected pore water samples across different months (August and November in 2017 and May 2018) with a gradient of water table changes and temperatures at the Dajiuhu peatland, Central China. The samples were analyzed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 104 publications
(110 reference statements)
2
4
0
Order By: Relevance
“…palmeri rhizosphere soils and native rhizosphere soils, respectively ( Figures 6A , B ). This outcome corroborated previous findings that keystone taxa play critical roles in controlling soil microbial functional capacity ( Zhang et al, 2019 ; Shi et al, 2020 ; Tian et al, 2021 ). Besides, we further found that the keystone taxa in A .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…palmeri rhizosphere soils and native rhizosphere soils, respectively ( Figures 6A , B ). This outcome corroborated previous findings that keystone taxa play critical roles in controlling soil microbial functional capacity ( Zhang et al, 2019 ; Shi et al, 2020 ; Tian et al, 2021 ). Besides, we further found that the keystone taxa in A .…”
Section: Discussionsupporting
confidence: 91%
“…We found that the keystone taxa best explained the functional genes with the explanation of 32.27 and 37.61% in A. palmeri rhizosphere soils and native rhizosphere soils, respectively (Figures 6A,B). This outcome corroborated previous findings that keystone taxa play critical roles in controlling soil microbial functional capacity (Zhang et al, 2019;Shi et al, 2020;Tian et al, 2021). Besides, we further found that the keystone taxa in A. palmeri rhizosphere soils were significantly positively correlated with the functional genes of soil microbial communities compared with native plants (Supplementary Figure S5A).…”
Section: Drivers Of Soil Functionssupporting
confidence: 91%
“…The autotrophs and heterotrophs were both abundant in S 1 –S 4 . The heterotrophs in S 1 –S 4 , including Ferruginibacter , Bacteroides , Trichococcus , Dokdonella , Herminiimonas , Sphingobium , and Cellulomonas , are associated with the degradation of organics or HD processes ( Chen et al, 2016 ; Han et al, 2020 ; Tian et al, 2021 ; Xin and Qiu, 2021 ; Zhang et al, 2021 ), and their abundances were both decreased or disappeared in S 5 –S 8 . The abundance of Rhodanobacter increased in R 1 and R 3 reactors, even though these bacteria are related to the degradation of carbohydrates ( Xin and Qiu, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Peat samples were collected in August 2017 from four Sphagnum -dominated sites: one each at Erhaoba and Niangniangfen, and two at Yangluchang, each with a different water table level. The water table level was determined with an Odyssey Logger (Dataflow Systems Limited, Christchurch) as previously described ( 43 ).…”
Section: Methodsmentioning
confidence: 99%